Characterization of microstructure and phase distribution of sintered multiphasic calcium phosphate bioceramics. Issue 4 (March 2020) - Stastny, Premysl; Vacek, Petr; Trunec, Martin
Abstract: The microstructures of sintered multiphasic calcium phosphate (CaP) ceramics with three initial hydroxyapatite to tricalcium phosphate ratios ranging from 1:4 to 4:1 were characterized at the grain scale. The grain structure, phase composition and spatial phase distribution in sintered calcium phosphate bioceramics were examined by the electron backscatter diffraction (EBSD) supplemented with X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. EBSD proved to be a powerful analytical tool for characterizing grain and phase distribution of CaP bioceramics. The EBSD grain maps connected with the EBSD phase analysis successfully described the phase distribution and grain microstructure of the sintered ceramics in detail. The change in the overall phase composition after sintering was explained by a chemical reaction between a phase impurity of TCP powder and HA. These results can lead to a better understanding of the mechanical and biodegradation properties of CaP bioceramics in both in-vivo and in-vitro conditions.